2011
DOI: 10.1097/aud.0b013e3182008c56
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Evoked Compound Action Potential Measures for Virtual Channels Versus Physical Electrodes

Abstract: Objectives-The number of distinct pitch percepts for cochlear implant (CI) listeners is somewhat limited by the number of physical electrodes in the array. Newer-generation CIs have the capability to potentially increase this number by stimulating areas of the cochlea between the physical electrodes. Currently this is achieved by electrically coupling adjacent electrodes or by simultaneously activating two electrodes with independent current sources (i.e., "current steering"). Presumably, either type of dual-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 27 publications
3
23
0
1
Order By: Relevance
“…ECAP amplitudes were then normalized for each subject according to the highest amplitude across the two physical-electrode probe functions within a set and separately for each region. This was done to preserve the spatial relationships among the probe SOEs being compared and to allow for SOE comparisons across electrode sets and subjects (Hughes, 2008;Hughes and Goulson, 2011;Hughes et al, 2013). Following methodology from Hughes (2008), the amount of spatial separation (R) among each of the pairs of SOE functions was quantified.…”
Section: Ecap Stimuli and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…ECAP amplitudes were then normalized for each subject according to the highest amplitude across the two physical-electrode probe functions within a set and separately for each region. This was done to preserve the spatial relationships among the probe SOEs being compared and to allow for SOE comparisons across electrode sets and subjects (Hughes, 2008;Hughes and Goulson, 2011;Hughes et al, 2013). Following methodology from Hughes (2008), the amount of spatial separation (R) among each of the pairs of SOE functions was quantified.…”
Section: Ecap Stimuli and Proceduresmentioning
confidence: 99%
“…The ECAP SOE function has been examined for virtual-channel stimulation (Busby et al, 2008;Saoji et al, 2009;Hughes and Goulson, 2011;SnelBongers et al, 2012;Hughes et al, 2013). These studies have shown that virtual channels produce ECAP SOE patterns similar to those of physical electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies (Pretorius andHanekom 2008, Goldsworthy et al 2013) have found CI discrimination thresholds between 5 and 30 %; furthermore, Vandali et al (2014) demonstrated that training can improve CI discrimination thresholds by more than a factor of 2. While the use of synthetic tones presented through the CI processor is relatively unexplored, there is a rich literature investigating CI pitch perception based on electrode psychophysics (Tong et al 1982;McDermott and McKay 1997;Hanekom and Shannon 1998;Zeng 2002;Henry and Turner 2003;Carlyon et al 2010;Hughes and Goulson 2011;Goldsworthy and Shannon 2014) as well as using more natural stimuli (Fujita and Ito 1999;Gfeller et al 2002;McDermott 2004;Looi et al 2008). In the present article, the suggestion put forth by Pretorius and Hanekom (2008) that pure and complex tones can be used to probe different aspects of perception is extended toward understanding correlations with phoneme identification in noise.…”
Section: Introductionmentioning
confidence: 99%
“…However, implanted adults and children are still experiencing problems in challenging listening situations, such as background noise or listening to music. One reason for this might be reduced spectral resolution caused by the limited number of physical electrodes in the array (Brendel et al 2009;Hughes and Goulson 2011). Dual electrode stimulation (DES), either simultaneous (Donaldson et al 2005;Townshend et al 1987) or sequential (Kwon and van den Honert 2006;McDermott and McKay 1994), has been proposed as a method to increase the number of perceivable pitches with CIs.…”
Section: Introductionmentioning
confidence: 99%